Impact of Expanding Window from Three Years to Five Years for Research Performance Parameter in India Rankings - Joorel, J P Singh; Solanki, Hiteshkumar; Kumar, Abhishek; Shah, Dharmesh; V, Raja; Trivedi, Kruti; Pradhan, Pallab; Singh, Priyanka (DESIDOC Journal of Library & Information Technology, 2021)
The India Rankings 2020 was announced the 5th annual edition of ranking for higher educational institutions in India based on National Institutional Ranking Framework (NIRF). The impact of NIRF among institutions is progressive on their output, outcomes, and outreach to the society. The government of India is also concentrating on several policy decisions in the education sector based on the results of India Rankings. This paper is focused on the study of Research Performance (RP) parameter on India Rankings while expanding five-years window instead of three-years window. Moreover, the study is also focused on Pearson correlation between three-years research performance score and five-years RP score and weighted score of institutions. It is attempted to derive the Spearman rank correlation between RP rank and overall rank based on all parameters score.